PRISMA-ScR: A scoping review of rooted resilience in advancing climate-adaptive agriculture for soil health and security - Eliakira Kisetu Nassary (Soil Security)
Climate change threatens agricultural productivity and soil health through rising temperatures, unpredictable rainfall, and land degradation. This scoping review aimed to map and synthesize evidence on adaptive agricultural practices that support soil functionality, resilience, and productivity, particularly in climate-vulnerable regions. Using the PRISMA-ScR framework, 1587 sources were screened, and 178 peer-reviewed articles were included for detailed analysis. The review identified key strategies such as cover cropping, organic amendments, reduced tillage, diversified cropping systems, agroforestry, and targeted nutrient management. Across diverse agroecological settings, these practices increased soil organic carbon by 8–25 %, improved water retention and microbial activity, and supported yield gains of 10–40 % under climate stress. Despite documented benefits, adoption remains limited due to economic constraints, knowledge gaps, and lack of enabling policies. Integrated approaches that blend scientific research with local knowledge and context-specific management have shown potential to strengthen soil resilience. Findings highlight the importance of healthy soils for climate-adaptive agriculture, food security, and ecosystem services. Enhancing adaptive soil management offers a pathway toward more resilient and sustainable farming systems in the face of ongoing climate change.